AN ANALYSIS ON LEARNING STRATEGIES OF SUCCESSFUL ENGLISH LEARNERS - Jannah, Wilda; Wardah, Wardah (FKIP - Universitas Tanjungpura, 2022)
This research aimed to describe language learning strategies used by the science 4 students whose English scores of 80 and above. The subject of this study was the successful English learners from the Eleventh Grade of Science 4 Students in SMAN 05 Pontianak. They are 10 students from Science 4. The design of this research was a case study. The data were collected through a questionnaire to determine the students